Bulges in G‑Quadruplexes: Broadening the Definition of G‑Quadruplex-Forming Sequences - Mukundan, Vineeth Thachappilly; Phan, Anh Tuân (Journal of the American Chemical Society, 2013)
We report on the first solution structure of an intramolecular G-quadruplex containing a single bulge and present evidence for extensive occurrence of bulges in different G-quadruplex contexts. The NMR solution structure of the d(TTGTGGTGGGTGGGTGGGT) sequence reveals a propeller-type parallel-stranded G-quadruplex containing three G-tetrad layers, three double-chain-reversal loops, and a bulge. All guanines participate in the formation of the G-tetrad core, despite the interruption between the first guanine and the next two guanines by a thymine, which forms a single-residue bulge and is projected out of the G-tetrad core. To provide a more general understanding about the formation of bulges within G-quadruplexes, we systematically investigated the effects of the residue type, the size, the position, and the number of bulges on the structure and stability of G-quadruplexes. The formation of bulges has also been observed in two different G-quadruplex scaffolds with different strand orientations and folding topologies. Our results show that bulges can be formed in many different situations within G-quadruplexes. While many sequences tested in this study can form stable G-quadruplex structures, all of them defy the description of sequences G3+NL1G3+NL2G3+NL3G3+, currently used in most bioinformatics searches for identifying potential G-quadruplex-forming sequences in the genomes. Broadening of this description to include the possibilities of bulge formation should allow the identification of more G-quadruplex-forming sequences which went unnoticed in the earlier searches. This study could also open the possibilities of exploiting bulges as recognition elements for interactions between G-quadruplexes and other molecules.